Review of Engaging language learners in contemporary classrooms; Authors: Sarah Mercer, Zoltán Dörnyei; Publisher: Cambridge University Press, 2020; ISBN: 9781108445924; Pages: 208 - Almukhaild, Haydab (Studies in Second Language Learning and Teaching, 2020)
Learner engagement is key to successful learning experiences in general education and language learning is no exception. When students are engaged, they are focusing on the task at hand, paying attention and enjoying their language learning (Aubrey et al., 2020; Ellis, 2018; Mercer, 2019; Oga-Baldwin, 2019). Yet, as Mercer and Dörnyei affirm in their introduction to the book, “discussions of engagement . . . have been largely absent from the literature of L2 [second language] learning and teaching” (p. 4). Engaging Language Learners in Contemporary Classrooms addresses this gap directly and in great depth, thus making it a ground-breaking contribution to the growing body of second language (L2) literature on learner engagement.